Investigations on tensile fractography and wear characteristics of Al7075-Al2O3-SiC Hybrid Metal Matrix Composites routed through liquid metallurgical techniques (Fracture and Structural Integrity, 2021)
The Al2O3-SiC reinforced Al7075 Metal Matrix Composite (MMCs) is fabricated through liquid metallurgical technique. Ceramic particulates were amalgamated into aluminium alloy to achieve improved mechanical properties and wear resistance. Al-7075/Al2O3/SiC hybrid MMCs were produced by reinforcing 2%, 3%, 4% and 5% of Al2O3 and 3%, 5% and 7% of SiC particles. Microstructural analysis was carried out to evaluate the uniform dispersal of reinforcing particulates within the base matrix. The output results indicate that the mechanical properties of the hybrid MMCs enhanced by increase the wt. % of ceramic particulates. Tensile fractography results show the internal fracture structure of the tensile test specimens in which the particulates fracture and pullouts were observed. The wear characteristics of developed composites are studied using pin on disc apparatus. The high wear resistance is observed at 5% Al2O3 + 7% SiC reinforced MMCs.
Keywords: Al7075; MMCs; Tensile; Fractography analysis; Hardness; Wear loss